Understanding the water use efficiency of sugar beet - Barratt, Georgina Elizabeth (2021)
Climate change threatens crop production globally and in Europe hotter and drier summers are predicted which will result in a reduction in crop yields due to increasingly limited water availability. A sufficient supply of water is crucial to maximising crop yield because dry matter accumulation is directly proportional to water use in many environments, as solar radiation drives both photosynthesis and transpiration. Water use efficiency (WUE) has been studied in many of the major crop species including rice, wheat and maize, as they are grown in a wide range of climates, including those with poor water availability. From this research more WUE varieties of wheat have been developed to enable production in areas where water is limiting. This highlights that understanding crop WUE is a useful endeavour and that research should be undertaken in less studied crop species. One such species is sugar beet which is usually either irrigated or grown in climates with sufficient water availability. As water availability becomes increasingly limited it would be beneficial to understand how sugar beet uses water to inform crop management and identify traits for breeders linked to greater WUE to make the crop more resilient. This thesis explores WUE in sugar beet from the leaf to the crop level in controlled environment room and polytunnel experiments to understand how the plant uses water. The three studies presented in this thesis have enabled sugar beet WUE to be characterised and have highlighted the anisohydric behaviour of the species. The first controlled environment study showed that sugar beet has fast stomatal responses compared to spinach which resulted in a similar level of intrinsic water use efficiency (WUEi), despite reaching higher rates of stomatal conductance (gs). The high rates of gs could be linked to the transient wilting of the crop in the field and the concurrently high rates of CO2 uptake and assimilation suggests wilting may not be detrimental to yield. Scaling up from the leaf level to the crop level, sugar beet were grown in large boxes in a polytunnel and exposed to four different irrigation regimes. Reduced water availability increased WUE (except in cases of extreme water limitation) and no acclimation (defined as permanent changes in physiology opposed to short term changes such as reduced leaf gas exchange) to water deficit was evident as the plants responded similarly to repeated drought. Full recovery was observed after drought and the sugar beet showed an ability to continue to photosynthesise, even under severe water deficit, which is likely attributed to its anisohydric characteristics. The most significant finding of the study was that varietal differences in WUEi and associated traits were evident, including a lower stomatal density, which could possibly be linked to canopy architecture. Following on from these studies, diurnal WUEi in sugar beet was characterised to identify when the crop is most and least WUE during the day, and if water deficit affected this response. It was shown that WUEi declines later in the day as light, and therefore assimilation, declines faster than gs. Water deficit increased WUEi and decreased the magnitude of the diurnal change in WUEi, as gs and A were reduced. The variety with greater WUEi in the second study also had higher WUEi in this study, but this did not lead to a greater dry matter WUE (WUEDM) in any of the experiments which may be due to small biomass sample sizes. Diurnal fluctuations in leaf water content were also evident, although the plants did not wilt due to diurnal changes but did under water deficit, however the diurnal changes in temperature and VPD were not as great as those observed in the field due to limitations of the growth chamber.